The Effect of Supra- and Subphysiologic Testosterone Levels on Ligature-Induced Bone Loss in Rats - A Radiographic and Histologic Pilot Study - Steffens, Joao P. [UNESP]; Coimbra, Leila S. [UNESP]; Ramalho-Lucas, Pablo D. [UNESP]; Rossa, Carlos [UNESP]; Spolidório, Luis Carlos [UNESP] (Amer Acad Periodontology, 2012)
Background: Testosterone is the primary male sexual hormone, and varying concentrations of the hormone mediated by physiologic, pathologic, or pharmacologic mechanisms may induce large variations in the body. Data regarding the general role of testosterone in mediating inflammation are still inconclusive. Therefore, the purpose of this study is to assess the consequences of supra- and subphysiologic levels of testosterone on ligature-induced bone loss in rats.Methods: Three male adult Holtzman rats were used to observe the course of serum testosterone concentration following orchiectomy (Ocx) and testosterone injections. Another 60 rats were randomly assigned to the following groups: 1) sham-operation controls (n = 10); 2) sham-operation and ligature-induced bone loss (n = 10); 3) orchiectomy without ligature (Ocx; n = 10); 4) Ocx and ligature (n = 10); 5) Ocx plus 250 mg/kg body weight intramuscular testosterone esters injection without ligature (Ocx+T; n = 10); and 6) Ocx, T, and ligature (n = 10). The ligatures were placed 30 days post-orchiectomy (or sham-operation) and maintained for 15 days. Thereafter, the rats were sacrificed, and their hemimandibles were used for radiographic evaluation of bone loss along with histologic and histometric analyses of gingival tissue.Results: The results indicated a significant increase in bone loss in the Ocx and Ocx+T groups in the presence and absence of inflammation, respectively. In addition, the Ocx and Ocx+T groups presented increased gingival area accompanying ligature-induced bone loss.Conclusions: Both sub- and supraphysiologic testosterone levels may influence bone metabolism, but only subphysiologic levels significantly increase ligature-induced bone loss. Moreover, testosterone has a regulatory effect on the gingival area. J Periodontol 2012;83:1432-1439.
Keywords: Bone remodeling; gingival overgrowth; inflammation; testosterone